Administration of Ashitaba (Angelica keiskei) Leaf Extracts Cream Prevented The Increase of MMP-1 Expression and The Decrease of Collagen Number in The Male Wistar Rats (Rattus norvegicus) Skin Exposed to UVB - Phery Candres; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Ultraviolet, especially the ultraviolet B (UV-B), is the most dominant cause of skin aging through increasing collagen degradation and activation of matrix metalloproteinase (MMPs). Recently, a lot of research focus on finding natural antioxidants with photoprotective activity. Ashitaba (Angelica keiskei) contains antioxidants and chalcone flavonoids. The purpose of this study was to examine the effect of ashitaba leaf extract, whether it could prevent increasing MMP-1 expression and decreasing collagen amount in rats exposed to UV-B rays. Methods: This study used randomized posttest only control group design. Subjects were 36 albino rats (Rattus norvegicus), male, adult (2.5 - 3 months old), weighing between 180-200 grams. All rats were divided into 18 rats each, namely the control group (the subject was smeared with basic cream and exposed to UVB) and the treatment group (the subject was smeared with ashitaba extract cream and exposed to UVB). The expression of MMP-1 using immunohistochemical staining and the amount of collagen using Sirius red staining. Results: The mean expression of MMP-1 in the control group was 28.14 ± 2.89% and in the treatment group was statistically lower at 9.45 ± 2.67% (p <0.001). The average amount of collagen in the control group was 53.64 ± 2.58% and in the treatment group was statistically higher at 83.57 ± 2.47% (p <0.001). Conclusion: The administration of ashitaba (Angelica keiskei) leaf extracts cream prevented the increase of MMP-1 expression and the decrease of collagen number in the male wistar rats (Rattus norvegicus) skin exposed to ultraviolet B.